PENGEMBANGAN MODUL PEMBELAJARAN MUATAN IPS BERBASIS KEARIFAN LOKAL KABUPATEN MALANG KELAS IV BAB 6 TOPIK A KEUNIKAN KEBIASAAN MASYARAKAT DI SEKITARKU - Anwar, Moh. Farid Nurul; Widodo, Wahyu; Rozhana, Kardiana Metha; Natalia, Ria (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2023)
The purpose of this development is to create a valid and effective learning module based on local wisdom in Malang Regency. The research method used is Research and Development (R&D) with the Borg And Gall model which has been modified and simplified into 7 stages, namely (1) initial information collection, (2) planning, (3) initial product format development, (4) expert validation, (5) product revision, (6) small group trials, (7) product revisions, (8) large group trials, and (9) valid and effective products. Development goes through two stages of validity involving 3 validator experts, namely material experts, linguists and design experts. In the small group trial involving 5 students and in the large group trial involving 10 students and homeroom teachers of SD Negeri 1 Landungsari. The validation results in the second stage are material experts 76% with valid criteria, linguists 92% with very valid criteria, 94% design experts with very valid criteria, it can be concluded that the module is very valid and very feasible for field trials without revision. The results of the teacher response questionnaire were 100% with very feasible criteria, the small group trial student response questionnaire 98.66% of the criteria were very feasible, the large group trial student response questionnaire 98.66% of the criteria were very feasible. The value of student learning outcomes of small group trials 96 with very effective criteria, in large group trials 97 with very effective criteria and achieved 100% completeness. From this value, it can be concluded that the social studies content learning module based on local wisdom of Malang Regency is declared valid and effective.